2016
DOI: 10.23860/mgdr-2016-01-01-07
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Goods Markets and Economy in China: A Historic Account

Abstract: Rapidly expanding virtual goods markets and virtual economy are thriving worldwide in general, and in China in particular. This paper reviews the growth of virtual goods markets in China and builds a historical narrative of the rapidly changing (or dynamic) and persistently unchanged (or relatively static) aspects of reality in China that condition virtuality and virtual goods markets. The review and historical analysis provide a perspective of a larger place -a total reality -where the virtuality and virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…This research provides various avenues for future research. First, our results provide insights into the Asian market using Korean data, keeping in mind that Asian customers occupy 70% of the total virtual goods market (Zhang, 2016). Research on cultural differences might give practitioners additional implications for social networking sites to expand their market scope (Jackson and Wang, 2013; Lee and Wohn, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This research provides various avenues for future research. First, our results provide insights into the Asian market using Korean data, keeping in mind that Asian customers occupy 70% of the total virtual goods market (Zhang, 2016). Research on cultural differences might give practitioners additional implications for social networking sites to expand their market scope (Jackson and Wang, 2013; Lee and Wohn, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Second, this study focuses on the actual purchase of virtual items driven by social network structures, while most prior studies have identified motivation and purchase intention. We analyzed field data from Cyworld to gain meaningful insights into the Asian virtual goods market (Zhang, 2016). Asia is the primary market for virtual goods sales, a part of the fundamental business model for many game services and SNSs (Balakrishnan and Griffiths, 2018;Hamari et al, 2017bHamari et al, , 2020Lehdonvirta and Castronova, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this dominant logic of consumerism present in the virtual goods market is often at odds with traditional values of non-Western countries. For instance, in China, globalization gave rise to individualism, hedonism, and a growth of virtual markets; however, traditional values of collectivism and government, media, and family constraints persist (Zhang 2016).…”
Section: Market Society and Video Gamesmentioning
confidence: 99%